PERAN PERAWAT DALAM PELAKSANAAN PERSONAL HYGIENE MENURUT PERSEPSI PASIEN IMOBILISASI FISIK - Dina Sulistyowati; Fitria Handayani (Jurusan Keperawatan, Universitas Diponegoro, 2012)
The nurse's role in providing nursing care should be implemented comprehensively, not only focus on promotive measures but also on the implementation of preventive measures such as personal hygiene, especially in patients with physical immobilization. Immobilization can affect a person's ability to move and the move to meet so the needs of personal hygiene can not be properly fulfilled. This research aims to determine the role of nurses in the implementation of personal hygiene by perception of patients with physical immobilization in surgical ward and internal disease ward RSUD Ungaran. This research used a questionnaire with checklist form about implementation of personal hygiene procedures that have been done validity test with r table value more than 0.361 and the reliability test with r value 0.816 which involved 141 respondents. This type of research is descriptive with purposive sampling techniques and analysis of research data using univariate analysis. The results of data analysis research were 77 respondents (54.6%) said good and 64 respondents (45.4%) said bad. In conclusion of the nurse’s role in implementation of personal hygiene by perception of physical immobilization patient’s research is 64 respondents (45.4%) said bad. Nurses should improve nursing services by providing the same facilities to all patients in the physical immobilization of personal hygiene needs